2014
DOI: 10.1155/2014/373104
|View full text |Cite
|
Sign up to set email alerts
|

Osseous Choristoma of the Tongue: A Review of Etiopathogenesis

Abstract: Osseous choristoma is a normal bone tissue in an ectopic position. In the oral region lingual localization occurs more frequently and the mass is generally localized on the dorsum of the tongue. Definitive diagnosis is obtained only after histopathologic examination. The etiology remains already debatable. The treatment of choice is surgical excision. In this paper we present a case of tongue osseous choristoma and a review of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 30 publications
1
39
0
9
Order By: Relevance
“…The diagnosis of "osteoma" were excluded from the review. Our review revealed 77 lingual osseous choristoma cases reported between 1971 -2017 ( in the trauma site give rise to the lesion [7]. In our case, the lesion consisted of mature bone tissue with fully developed Haversian system and not just calcification.…”
Section: Discussion and Review Of The Literaturementioning
confidence: 62%
“…The diagnosis of "osteoma" were excluded from the review. Our review revealed 77 lingual osseous choristoma cases reported between 1971 -2017 ( in the trauma site give rise to the lesion [7]. In our case, the lesion consisted of mature bone tissue with fully developed Haversian system and not just calcification.…”
Section: Discussion and Review Of The Literaturementioning
confidence: 62%
“…Lingual osseous choristoma is mostly (71%) located beside the foramen caecum and circumvallate papilla in the posterior 1/3 of the tongue. Less frequently, it is located in the lateral edge of the tongue and in the middle 1/3 of the tongue (at rates of 17% and 6%, respectively) (3,4). In 1931, Liu and Tan (7) published a case of bilateral osseous choristoma located on both sides of the foramen cecum.…”
Section: Introductionmentioning
confidence: 99%
“…Lingual osseous choristoma is seen in the age range of 5 to 73 years, particularly between the ages of 20 to 50, and the mean age of patients is 28.7 years (3-6). The frequency of lingual osseous choristoma is 2.7-4 times higher among females than among males (3,(5)(6)(7). In our case, the patient was a 41-year-old female, which was consistent with the literature expectation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations